NF-κB signaling in skin aging. (December 2019) - Wang, Yujia; Wang, Lian; Wen, Xiang; Hao, Dan; Zhang, Nan; He, Gu; Jiang, Xian
Highlights: Aging skin tissue created a permissive tissue microenvironment. The microenvironment promoted SASP activation. SASP activation promoted the initiation, progression, resistance of cancer cells. NF-κB plays a key role in SASP. NF-κB pathway is of vital importance in skin aging. Abstract: Skin is the largest organ of the body, and is prone to be affected by external environmental factors. Skin aging is caused by both genetic and environmental factors. Furthermore, aging skin tissue is known to create a permissive tissue microenvironment that promotes the initiation, progression and resistance of cancer cells by promoting the senescence-associated secretory phenotype (SASP). Therefore, more attention should be paid to skin aging. In this review, we highlight the common Rel proteins and two activation pathways: the canonical activation pathway and the non-canonical activation pathway. Furthermore, we summarize the role of NF-κB in skin aging. The effects of UV on the skin results from the production of ROS. Excessive free radicals activate the NF-κB signaling pathway and MAPK signaling pathway, contributing to the activation of AP-1 and NF-κB. Then it increased the level of TNF-α and the expression of MMPs, which induce the degradation of ECM and accelerated skin aging. We also summarize some reported natural antioxidants and synthetic antioxidants which are related to NF-κB signals. On the other hand, NF-κB plays a key role in SASP. Upon senescence-inducing signals, ATM and ATR block p62-dependent autophagic degradation of GATA4, contributing to NF-κB activation and SASP induction.